2019
DOI: 10.3389/fmicb.2019.00119
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Bacteria Involved in Manganese(II) Oxidation and Removal From Groundwater

Abstract: The presence of iron (Fe) and manganese (Mn) in groundwater is an important concern in populations that use it as source of drinking water. The ingestion of high concentrations of these metals may affect human health. In addition, these metals cause aesthetic and organoleptic problems that affect water quality and also induce corrosion in distribution networks, generating operational and system maintenance problems. Biological sand filter systems are widely used to remove Fe and Mn from groundwater since they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 53 publications
(76 reference statements)
4
62
0
4
Order By: Relevance
“…These results are in agreement with previous findings for different MOB than the ones reported here, suggesting that during the stationary phase biological oxidation of Mn(II) takes place. 25,35,[66][67][68][69][70][71][72] In the second group of strains (HAC-3A, HAC-3B and RUE-6A), Fig. 2A, no further Mn(II) removal took place after the second day.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…These results are in agreement with previous findings for different MOB than the ones reported here, suggesting that during the stationary phase biological oxidation of Mn(II) takes place. 25,35,[66][67][68][69][70][71][72] In the second group of strains (HAC-3A, HAC-3B and RUE-6A), Fig. 2A, no further Mn(II) removal took place after the second day.…”
Section: Resultsmentioning
confidence: 96%
“…30,33 Moreover, they are catalytic agents for secondary oxidation reactions of Mn(II) that depend on Mn(II) concentration, temperature and other ions, among others. 32 Furthermore, the biofilm formation capacity of Mn oxidizing bacteria (MOB) immobilizes them in the filter material, 34,35 through their EPS matrix, and thus tolerates the environmental and mechanical conditions of the biofilters 27,28 and contributes to the adsorption of metals. 26,[36][37][38][39] Biological removal of Mn can be carried out by: 7,32 (a) direct oxidation, through intracellular oxidation of Mn(II) as part of the metabolic pathway of the microorganism; (b) indirect oxidation as a result of a change of the surrounding aqueous environment (pH and redox potential) and/or by the release of metabolic end products that favour the chemical oxidation of Mn(II); (c) extracellular adsorption of Mn on negatively charged EPS, as well as on biogenic oxides formed by bacterial catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mn is mainly present in reduced forms and their removal is mostly based on chemical oxidation that could be performed through induction of the oxidation of these metals to form insoluble oxides or the addition of strong oxidizing agents [39,40]. Manganese‐tolerant PGPR could be used to decrease the concentration and effects of this metal from contaminated sites in an environmental‐friendly manner, thereby improving the growth and health of the host plants.…”
Section: Discussionmentioning
confidence: 99%
“…And manganese pollution in a low concentration need microorganism to remove thoroughly. Many kinds of bacteria can transform thoroughly the Mn(II) to its oxides [11]. It is reported that kinds of manganese-oxidizing bacteria (MOB) harbour multicopper oxidase (MCO)-type enzyme or heme peroxidase [12,13] with the capacity of oxidization the soluble Mn(II) to insoluble Mn(IV).…”
mentioning
confidence: 99%